EVALUATION OF A LOCAL GOVERNMENT DEVELOPMENT PLANNING: THE CASE OF LATGALE - Ežmale, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Spatial planning is a practical and useful instrument introduced by the European Community and national governments throughout the last decade with the aim to promote development of regions and reach territorial cohesion. In order to assess interconnections between quality of spatial planning documents of local governments of Latgale region and territorial development indicators the following tasks were performed: to describe the methodology for evaluation the quality of spatial planning documents, to describe the results of interconnections between quality of spatial planning documents in local governments of the region and development indicators.